Tom and Jerry meet Sherlock Holmes : original movie [videorecording (DVD)] - Brandt, Spike; Siergey, Jeff; Kress, Earl; McDowell, Malcolm; York, Michael, 1942-; Rhys-Davies, John; DeLisle, Grey; Bergman, Jeff; Lamarr, Phil, 1967-; Ellis, Greg; Harnell, Jess; McGonagle, Richard; et al. (Warner Home Video, 2010)
Tom and Jerry team up with Sherlock Holmes to solve a mystery involving some sinister felines.